DA'WAH EXPERIENCE, SPIRITUAL, AND ECONOMIC RESILIENCE OF JAMAAH TABLIGH IN LANGSA ACEH - Muhammad Dayyan; Ainun Mardhiah; Masdalifah Sembiring (Universitas Islam Negeri Ar-Raniry, 2019)
This article examines the experience of da'wah, spirituality and economic resilience of jamaah tabligh in Langsa City. Jamaah Tabligh is a community that consistently carries out its da'wah to invite people to worship Allah Almighty by praying in congregation in mosques. The method of da'wah is done in the form of going to people's homes, traveling out of the area where they live by leaving their families in between two days, a week or even 40 days known as khuruj. Through observation of da'wah activities and family conditions, interviews with 5 males and 5 female jamaah tabligh families and one focus group discussion found that da'wah experiences, spiritual experiences and economic resilience of the jamaah tabligh families. That da'wah experiences face a number of challenges in the form of rejection and expulsion from the community faced calmly and patiently. The spiritual experience of increasing the sense of faith in the form of belief in the mercy of Allah has had an impact on the tranquility of the life of the family of the congregation. In terms of family economic resilience by the standards of dharuriyah and hajjiyah it has been fulfilled through savings, assistance from other jamaah members and side jobs by the wife of the jamaah.